2014
DOI: 10.1177/2050312114532079
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio is associated with low high-density lipoprotein cholesterol in healthy young men

Abstract: Objective:It has been reported that the neutrophil–lymphocyte ratio is significantly elevated in patients with low high-density lipoprotein cholesterol (<35 mg/dL). But in this study, some patients had hypertension that may have affected the neutrophil–lymphocyte ratio. This study consisted of 1274 asymptomatic healthy young men. In contrast with the previous study, we investigated the neutrophil–lymphocyte ratio in healthy young men with low high-density lipoprotein cholesterol compared with controls.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In spite of their clear role in coronary atherosclerosis very few studies have addressed the type of relationship between NLR, PLR, and HDL-C levels in CAD patients. A study conducted on healthy, asymptomatic, young males showed higher levels of NLR among the individuals with low HDL-C, which is in accordance with our study [ 28 ]. Though there is no previous reporting of PLR and HDL-C association, high PLR has also emerged as an independent predictor of long-term survival of patients having myocardial infarction [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…In spite of their clear role in coronary atherosclerosis very few studies have addressed the type of relationship between NLR, PLR, and HDL-C levels in CAD patients. A study conducted on healthy, asymptomatic, young males showed higher levels of NLR among the individuals with low HDL-C, which is in accordance with our study [ 28 ]. Though there is no previous reporting of PLR and HDL-C association, high PLR has also emerged as an independent predictor of long-term survival of patients having myocardial infarction [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, NLR is associated with pro-inflammatory mediators (high sensitive CRP, tumor necrosis factor-α) and progressive subclinical atherogenesis [24].A high NLR is a predictor of atherosclerosis progression [10,25,26] and long-term prognosis in patients after PCI [12]. As a protective factor for blood vessels, HDL-C has been observed in both healthy people [14] and CAD patients [15] as associated with NLR levels at lower levels. However, few authors have focused on the relationship between variability in blood lipids and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the typical white blood cell count range, a higher NLR is associated with atherosclerotic events [13]. In both healthy people [14] and coronary artery disease (CAD) patients [15], low HDL-C has been shown to correlate with the rise of NLR, although whether the variability of lipid protein has any effect on NLR remains unclear.…”
Section: Introductionmentioning
confidence: 99%